Gelechia nigrovittata Schantz, 1971 —- синоним G. jakovlevi Krulikowsky, 1905 (Lepidoptera, Gelechiidae) - Пискунов, В.И. (Вестник зоологии, 1977)
The article deals with results of studies of nine type samples of Gelechia jakovlevi K, r u 1. (males) kept at the Zoological museum of the Kiev State University (collection of L. Krulikovskij) and 1 male from the town of Svencioniliai in the Lithuanian SSR (collection of the Institute of Zoology and Parasitology of the Academy of Sciences of the Lithuanian SSR, Vilnius) and 1 female of this species from the Leningrad environs (collection of the Zoological Institute of the Academy of Sciences of the USSR, Leningrad). The lectotype is distinguished, a sample from the town of Malmisch caught on August 2, 1898 (collection number 14593). When studying genitals of the lectotype and a paralectotype it was determined that G. jakovlevi K r u I. is identical with C. nigrovittata Schantz described from Finland and the Latvian SSR. Therefore G. nigrovittata Schantz is reduced to synonym of G. jakovlevi K r u 1.